Giant Cell Granulomas of Jaws: a Clinicopathologic Study - Shruti Gupta; Anjali Narwal; Mala Kamboj; Anju Devi; Anita Hooda (Stilus Optimus, 2019)
Objectives: The purpose of present study was to investigate and correlate the histological findings in central giant cell granuloma and peripheral giant cell granuloma of jaws with clinical and radiographic interpretations of the lesion. Material and Methods: In present study, data from 14 cases of central giant cell granuloma (CGCG) and 9 cases of peripheral giant cell granuloma (PGCG) were analysed, focusing on demographic, clinical and radiographic features. For each patient, microscopic slides were assessed in terms of histologic features of giant cells i.e. number of giant cells, mean number of nuclei/giant cell, pattern of distribution, size and relative size index of giant cells, percentage fractional surface area (FSA) occupied by giant cells and stromal characteristics. Data collected was subjected to statistical analysis. Fisher-exact test, Pearson's correlation coefficient, one-way ANOVA test and Student's t-test were used for analysis. Results: No significant difference was found between PGCG and CGCG in relation to all the traits that were evaluated. It was observed that mean number of giant cells and mean FSA was more in aggressive CGCG as compared to non-aggressive CGCG. Conclusions: Further studies on large sample size are required to confirm the relationship between histomorphometric features of giant cells and behaviour of giant cell granulomas of jaws.